Investigating well-being, work limitations and preferences for self-management education and peer support among younger people with hip and knee osteoarthritis: protocol for a cross-sectional study - Ackerman, Ilana N (BMJ Publishing Group, 2013)
INTRODUCTION: Osteoarthritis (OA) has traditionally been considered a condition of older age. However, younger people are also affected by hip and knee OA, often as a result of sporting and work-related injuries. As OA studies have generally focused on older individuals, little is known about the experience of younger adults with hip or knee OA who can face a distinct set of pressures including work responsibilities and parenting roles. This study aims to investigate well-being and work participation among younger people with hip or knee OA, as well as preferences for OA education and support. METHODS AND ANALYSIS: 200 people aged 20–55 years with a diagnosis of hip and/or knee OA will be recruited for this cross-sectional study. Participants will be recruited from three major public hospitals in the state of Victoria, Australia following screening of orthopaedic outpatient clinic lists and referrals, and through community-based advertisements. A study questionnaire will be mailed to all participants and written informed consent obtained. Validated measures of Health-Related Quality of Life (HRQoL), health status, psychological distress and work limitations will be used. Information on health services use will be collected, in addition to information on the perceived utility and accessibility of a range of existing and proposed education and peer support models. HRQoL data will be compared with Australian population norms using independent t tests, and associations between HRQoL, health status, psychological distress, work limitations and demographic factors will be evaluated using univariate and multivariate analyses. Data on the perceived utility and accessibility of education and peer support models will be analysed descriptively. ETHICS AND DISSEMINATION: Ethics approval for the study has been obtained. The study findings will be submitted to peer-reviewed journals and arthritis consumer organisations for broader dissemination, and presented at national and international scientific meetings.